Application of plasma-combined regeneration technology in managing facial acne scars. (3rd April 2019) - Tian, Ju; Lei, Xiao Xuan; Xuan, Li; Tang, Jian Bing; Cheng, Biao
ABSTRACT: Background and Objectives : Plasma skin regeneration (PSR) and platelet-rich plasma（PRP） have gained popularity in the treatment of acne scars due to their efficacy and improved tolerability. The objective of this investigation was to evaluate the synergistic effect of PRP plus PSR (plasma-combined regeneration technology, PCRT) in managing facial acne scars. Methods : From March 2015 to June 2017，a total of 25 cases with facial atrophic acne scars were treated with PCRT treatment for three to five times. Treatments were repeated at an interval of 8 weeks．Treatment parameters were titrated to an immediate end point of moderate erythema. The clinical end point for cessation of treatment was the attainment of satisfactory clinical results. Results were monitored photographically up to 6 months after treatment. The efficacy and adverse effects were evaluated by using the following outcome parameters： the duration of edema, erythema and crusting; the degree of hyperpigmentation, hypopigmentation and scarformation; subjective effective rate was evaluated by patients and physicians. Results : 22 of 25 participants completed the study, and were followed up for 6–12 months. After three to five treatments, evaluation by patients showed that the total effective rate was 90.91%. Evaluation by two physicians showed that the total effective rate was 86.36%. Treatment was well tolerated by all participants. The total duration of side effects was 6.7 ± 1.7 days of edema, 8.1 ± 2.3 days of erythema, 6.5 ± 1.8 days of crusting, respectively. No hyperpigmentation, depigmentation, and worsening of scarring were observed by the conclusion of the follow-up period． Conclusion : These results provide initial evidence for the safety and effectiveness of PCRT as a well-tolerated modality for the treatment of acne scars. PCRT is an ideal treatment for facial acne scars with minimal side effect．